Pengaruh penggunaan bahan aditif berbeda terhadap kualitas fisik silase berbahan dasar rumput benggala (Panicum maximum) - Selfiana Pasi, Maria; Sio, Stefanus; Viktoria Tae, Agustina; Agung Dethan, Agustinus; M. C. noach, Steffanie; Usfinit, Gaudensiana (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2025)
The research was conducted in July - August 2023 at the Laboratory of the Faculty of Agriculture, Timor University, with the aim of determining the physical quality of silage made from panicum maximum with different additives added. The study used a Completely Randomized Design (CRD) to test the physical quality of silage made from panicum maximum consisting of 4 treatments and 4 replications. The treatments given are as follows: T0: Panicum maximum (Without additives/control), T1: Panicum maximum + 10% bran, T2: Panicum maximum + 10% Corn Flour, T3: Panicum maximum + 10% Brand pollard. The percentage of additives is calculated based on the weight of chopped panicum maximum. The variables studied were Color, Aroma, Texture, Fungi and pH. The results showed that the use of different additives affected the nutritional value of panicum maximum silage, indicating that Color, Aroma had a significant effect on other higher pollard additives (P<0.05), while Texture, Fungi and pH had no significant effect (P>0.05). It can be concluded that silage made from panicum maximum added with rice bran, corn flour, and pollard bran additives produces relatively the same texture, fungi, and pH content. However, the use of pollard can increase the color content of silage. The use of panicum maximum forage can increase the dry matter content of silage; it is better to use corn flour as an additive to increase the pH of silage.